Photoresist main body material, preparation method thereof, photoresist composition containing photoresist main body material and photoresist coating
By performing group modification and grafting reaction on carbon quantum dots, a photoresist host material based on carbon quantum dots was developed, which solved the problems of excessive size of existing photoresist molecules and poor etch resistance. A photoresist material with high resolution and low line edge roughness is achieved.
Patent Information
- Application Number
- CN202411647474.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-21
AI Technical Summary
The existing photoresist molecules are too large in size and have poor etch resistance, which limits their application in the preparation of nano-level patterns.
Using a photoresist host material based on carbon quantum dots, group modification is performed at the side end of the carbon quantum dot, and the arylsulfonium salt group is grafted through the Gunberg-Bachmann reaction to obtain high tilting resistance. Photoresist material with erosion properties.
The high resolution, low line edge roughness and good etch resistance of the photoresist are achieved, and the introduction of metal elements is avoided to contaminate the photolithography processing devices.
Smart Images

Figure CN119490443A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photolithography materials, and more specifically, to a photoresist main material, a preparation method thereof, and a photoresist composition and a photoresist coating containing the same. Background Art
[0002] With the rapid development of the semiconductor industry, the integration of semiconductor devices is getting higher and higher, and the resolution required for lithography technology is also getting higher and higher. The quality of high-resolution lithography patterns also puts forward higher requirements, especially the line width roughness (LWR) and line edge roughness (LER) of the patterns. The requirements are becoming more and more stringent.
[0003] Photoresist is a key material for transferring photolithographic patterns during semiconductor device processing. When photoresist is coated on different substrates and irradiated with energy such as light beams, electron beams, ion beams or x-rays, its solubility changes, and the corresponding pattern is transferred to the substrate through development and etching processes. Therefore, the resolution of the pattern formed by photoresist has a huge impact on the integration of the device.
[0004] In order to meet the characteristics and requirements of photolithography, polymer materials, single-molecule resin materials and metal nanocomposite materials are designed and synthesized for use in the field of high-resolution photolithography, which lays the foundation for obtaining photoresist materials with high resolution, high sensitivity and low line edge roughness. However, as the research goes deeper, it is found that the molecular volume of polymer photoresist is large and the molecular weight distribution is uneven, which affects the resolution of photoresist and limits its application in preparing nanometer-level patterns. Although the molecular size of single-molecule resin is small, it is conducive to improving the resolution of photoresist, but usually its synthesis process is complicated, and according to the law that the higher the carbon-hydrogen element ratio in the photoresist, the stronger the etching resistance, it can be predicted that the etching resistance of single-molecule resin is limited. Since metal elements are introduced into metal nanoparticle materials, the etching resistance is improved, and it also has the advantages of high resolution, high sensitivity and easy preparation, but the dissociation of metal ions in the photolithography process and the residue of metal glue may cause processing device pollution.
[0005] Carbon quantum dots are a kind of sp 2 / sp 3 Carbon nanomaterials with a size of less than 10 nm, which are composed of the core and attached states of hybrid carbon atoms, have attracted widespread attention due to their low cost, low pollution, easy preparation, low toxicity, and good photostability. Therefore, it is of scientific significance and application prospect to develop a new type of photoresist material with low molecular weight, good etching performance, easy preparation, and strong etching resistance based on the structural characteristics of carbon quantum dots. Summary of the invention
[0006] The first object of the present invention is to provide a photoresist main material based on carbon quantum dots. The photoresist main material has a small particle size and a narrow particle size distribution, which is conducive to preparing high-resolution patterns, and has a high carbon content, which can enhance the etching resistance of the photoresist without introducing metal elements.
[0007] The second object of the present invention is to provide a method for preparing a photoresist main material based on carbon quantum dots.
[0008] The third object of the present invention is to provide an application of the above-mentioned photoresist main material in preparing photoresist.
[0009] A fourth object of the present invention is to provide a photoresist composition.
[0010] A fifth object of the present invention is to provide a photoresist coating.
[0011] A sixth object of the present invention is to provide an application of the photoresist coating as described above in photolithography.
[0012] In order to achieve the above first object, the present invention adopts the following technical scheme:
[0013] The present invention discloses a photoresist main material based on carbon quantum dots, and the general structure of the photoresist main material is as follows:
[0014]
[0015] Among them, R A Selected from H, C 1-15 Alkyl, C 1-15 Alkoxy, C 3-20 Any one of a cycloalkyl group and a 3- to 20-membered heterocyclic group;
[0016] R B , R C The same or different, independently selected from H, C 1-15 Alkyl, C 3-20 Cycloalkyl, C 6-20 aryl, 5- to 20-membered heteroaryl, 3- to 20-membered heterocyclyl, -C 1-15 Alkyl-C 6-20 Aryl, -C 1-15 Alkyl-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 6-20 Aryl, -C 1-15 Alkyl-CO-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 1-15 Alkyl, -C 1-15 Alkyl-CO-C 3-20Any of the cycloalkyl groups;
[0017] X - represents an anion selected from any one of halide, carboxylate, sulfate, alkyl sulfonate, haloalkyl sulfonate, p-toluenesulfonate, tetrafluoroborate, hexafluoroantimonate, hexafluorophosphate, and bis(trifluoromethanesulfonyl)imide;
[0018] It represents the structure of carbon quantum dots with side groups. It should be noted that, in the preparation process of the photoresist main material, the COOH group on the carbon quantum dots will be modified by other functional groups. In order to better represent the modification relationship of the side groups, the carboxyl groups on the carbon quantum dots are drawn and expressed in the above form.
[0019] In the present invention, the self-made carbon quantum dots are used as the core and the side groups are modified (i.e. -COOR A -end), and the arylsulfonium salt group was grafted onto the core sp of the carbon quantum dot through the Gomberg-Bachmann reaction. 2 / sp 3 On carbon atoms, a photoresist main body material is obtained, which retains the original typical characteristics of carbon quantum dots, such as small particle size, narrow particle size distribution, high carbon content, etc., thereby effectively solving the problems of existing photoresist molecules being too large and having poor etching resistance. In addition, since the prepared photoresist main body material contains polar functional groups, it can be dissolved in polar solvents. When the photoresist film prepared in this way is exposed, the polar sulfonium salt functional groups decompose, reducing the polarity of the polymer, thereby generating solubility differences and forming photolithographic patterns. Therefore, when a solvent with a larger polarity is selected for development, the photoresist composition prepared using the photoresist main body material can be used as a negative photoresist; if a solvent with a relatively small polarity is selected for development, the photoresist composition prepared using the photoresist main body material can be used as a positive photoresist. In addition, technicians can also conveniently and quickly adjust the groups connected to the carbon atom points to change the photophysical properties and photolithographic performance of the photoresist main material according to application needs, thereby affecting the performance of the photoresist composition.
[0020] The term "C 1-15 "Alkyl" is understood to mean a straight-chain or branched saturated monovalent hydrocarbon radical having 1 to 15 carbon atoms. For example, "C 1-6The term “alkyl” refers to straight-chain and branched alkyl groups having 1, 2, 3, 4, 5 or 6 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl or 1,2-dimethylbutyl, or the like or isomers thereof.
[0021] The term "C 1-15 "Alkoxy" is understood to mean -OC 1-15 Alkyl, where C 1-15 Alkyl has the above definition.
[0022] The term "C 3-20 "Cycloalkyl" should be understood to mean a saturated monovalent monocyclic, bicyclic hydrocarbon ring or polycyclic hydrocarbon ring (also called condensed hydrocarbon ring) having 3-20 carbon atoms. Bicyclic or polycyclic cycloalkyl groups include paracyclic cycloalkyl, bridged cycloalkyl and spirocyclic cycloalkyl; the paracyclic refers to a condensed ring structure formed by two or more cyclic structures sharing two adjacent ring atoms (i.e., sharing one bond). The bridged ring refers to a condensed ring structure formed by two or more cyclic structures sharing two non-adjacent ring atoms. The spirocyclic refers to a condensed ring structure formed by two or more cyclic structures sharing one ring atom. For example, the C 3-20 The cycloalkyl group may be selected from C 3-8 Monocyclic cycloalkyl, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, or C 7-12 Cycloalkyl, such as decahydronaphthalene; it can also be C 7-12 Bridged ring cycloalkyl, such as norbornane, adamantane, bicyclo[2,2,2]octane.
[0023] The term "3 to 20-membered heterocyclyl" means a saturated or unsaturated monovalent monocyclic or bicyclic hydrocarbon ring, and contains 1-5 heteroatoms independently selected from N, O or S, preferably a "3 to 10-membered heterocyclyl". The term "3 to 10-membered heterocyclyl" means a saturated monovalent monocyclic or bicyclic hydrocarbon ring, and contains 1-5, preferably 1-3 heteroatoms selected from N, O or S. The heterocyclyl may be connected to the rest of the molecule through any one of the carbon atoms or the nitrogen atom (if present). In particular, the heterocyclyl may include, but is not limited to: a 4-membered ring, such as azetidinyl, oxetanyl; a 5-membered ring, such as tetrahydrofuranyl, dioxolyl, pyrrolidinyl, imidazolidinyl, pyrazolidinyl, pyrrolinyl; a 6-membered ring, such as tetrahydropyranyl, piperidinyl, morpholinyl, dithianyl, thiomorpholinyl, piperazinyl or trithianyl; a 7-membered ring, such as diazepanyl. Optionally, the heterocyclic group may be benzo-fused. The heterocyclic group may be bicyclic, such as, but not limited to, a 5,5-membered ring, such as a hexahydrocyclopenta[c]pyrrole-2(1H)-yl ring, or a 5,6-membered bicyclic ring, such as a hexahydropyrrolo[1,2-a]pyrazine-2(1H)-yl ring. The ring containing nitrogen atoms may be partially unsaturated, i.e., it may contain one, two or more double bonds, such as, but not limited to, 2,5-dihydro-1H-pyrrolyl, 4H-[1,3,4]thiadiazinyl, 4,5-dihydrooxazolyl or 4H-[1,4]thiazinyl, or it may be benzo-fused, such as, but not limited to, dihydroisoquinolyl, 1,3-benzoxazolyl, 1,3-benzodioxolyl. According to the present invention, the heterocyclic group is non-aromatic.
[0024] The term "C 6-20 "Aryl" is understood to mean a monovalent aromatic or partially aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring having 6 to 20 carbon atoms, preferably "C 6-14 The term "C 6-14 The term "aryl" is understood to mean preferably a monovalent aromatic or partially aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring ("C 6-14 A "C6 aryl" group is a group having 6 carbon atoms, for example phenyl or biphenyl, or a group having 9 carbon atoms, for example indanyl or indenyl, or a group having 10 carbon atoms, for example indanyl or indenyl. 10 aryl), such as tetrahydronaphthyl, dihydronaphthyl or naphthyl, or a ring having 13 carbon atoms ("C 13 aryl), such as fluorenyl, or a ring having 14 carbon atoms ("C 14 aryl”), such as anthracenyl. When the C 6-20When the aryl group is substituted, it may be monosubstituted or polysubstituted. Also, there is no limitation on the substitution position, for example, it may be substituted at the ortho position, para position or meta position.
[0025] The term "5- to 20-membered heteroaryl" is understood to include monovalent monocyclic, bicyclic or tricyclic aromatic ring systems having 5-20 ring atoms and containing 1-5 heteroatoms independently selected from N, O or S, for example "5- to 14-membered heteroaryl". The term "5- to 14-membered heteroaryl" is understood to include monovalent monocyclic, bicyclic or tricyclic aromatic ring systems having 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14 ring atoms, in particular 5 or 6 or 9 or 10 carbon atoms, and containing 1 to 5, preferably 1 to 3 heteroatoms each independently selected from N, O and S and, in addition, in each case may be benzo-fused. In particular, the heteroaryl group is selected from thienyl, furanyl, pyrrolyl, oxazolyl, thiazolyl, imidazolyl, pyrazolyl, isoxazolyl, isothiazolyl, oxadiazolyl, triazolyl, thiadiazolyl, thia-4H-pyrazolyl and the like and benzo derivatives thereof, such as benzofuranyl, benzothienyl, benzoxazolyl, benzisoxazolyl, benzimidazolyl, benzotriazolyl, indazolyl, indolyl, isoindolyl and the like; or pyridyl, pyridazinyl, pyrimidinyl, pyrazinyl, triazinyl and the like and benzo derivatives thereof, such as quinolyl, quinazolinyl, isoquinolyl and the like; or azinyl, indolizinyl, purinyl and the like and benzo derivatives thereof; or cinnolinyl, phthalazinyl, quinazolinyl, quinoxalinyl, naphthyridinyl, pteridinyl, carbazolyl, acridinyl, phenazinyl, phenothiazinyl, phenoxazinyl and the like.
[0026] The above term “C 1-15 The definition of "alkyl" also applies to other C-containing 1-15 Alkyl groups, such as -C 1-15 Alkyl-C 6-20 Aryl, -C 1-15 Alkyl-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 6-20 Aryl, -C 1-15 Alkyl-CO-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 1-15 Alkyl, -C 1-15 Alkyl-CO-C 3-20 Cycloalkyl, etc.
[0027] Similarly, C 6-20 Aryl, 5- to 20-membered heteroaryl, C 3-20 Cycloalkyl has the same definition throughout.
[0028] Furthermore, the R A Select from H or C 1-8 alkyl;
[0029] The R B Selected from H, C 1-6 Alkyl, C 6-12 Any of the aromatic groups;
[0030] The R C Select from H or C 1-8 alkyl.
[0031] Further, the photoresist main material is selected from one of the following structures:
[0032]
[0033] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0034] The present invention discloses a method for preparing the above-mentioned photoresist main material. In the preparation process, homemade carbon quantum dots are used as raw materials for preparation, and a new photoresist main material is obtained by performing group modification on the side base end of the carbon quantum dots. The method specifically comprises the following steps:
[0035] Dissolve compound 1 in a hydrochloric acid aqueous solution, cool to 0-5°C, add sodium nitrite, react for 0.5-1 hour, add a sodium hydroxide aqueous solution to obtain a reaction solution;
[0036] The reaction solution was added into a carbon quantum dot aqueous solution for reaction, and the compound P1 was obtained after freeze-drying;
[0037] Dissolve compound P1 in a solvent, add compound 2 and 4-dimethylaminopyridine, stir in an oil bath, react for 18-20 hours, extract the product with ethyl acetate, wash with water, dry the organic phase over sodium sulfate, and remove the solvent by rotary evaporation to obtain compound P2;
[0038] Compound P2 is added to a solvent, and compound 3 is added, reacted at room temperature for 12-24 hours, filtered, and the filtrate is concentrated by rotary evaporation and recrystallized to obtain a compound of formula I;
[0039] Wherein, the structures of compounds 1-3, P1, and P2 are as follows:
[0040]
[0041] R A Selected from H, C 1-15 Alkyl, C 1-15 Alkoxy, C 3-20 Any one of a cycloalkyl group and a 3- to 20-membered heterocyclic group;
[0042] R B , R C The same or different, independently selected from H, C1-15 Alkyl, C 3-20 Cycloalkyl, C 6-20 aryl, 5- to 20-membered heteroaryl, 3- to 20-membered heterocyclyl, -C 1-15 Alkyl-C 6-20 Aryl, -C 1-15 Alkyl-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 6-20 Aryl, -C 1-15 Alkyl-CO-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 1-15 Alkyl, -C 1-15 Alkyl-CO-C 3-20 Any of the cycloalkyl groups;
[0043] X is selected from any one of halogen, carboxyl, sulfonyl, alkylsulfonyl, halogenated alkylsulfonyl, p-toluenesulfonyl, tetrafluoroboric acid, hexafluoroantimonic acid, hexafluorophosphate, and bis(trifluoromethanesulfonyl)imide groups.
[0044] Further, the molar ratio of the compound 1, sodium nitrite and carbon quantum dots is 1:0.8-1.2:0.1-1;
[0045] The molar ratio of the compound P1, the compound 2 and 4-dimethylaminopyridine is 1:1-10:0.1-1;
[0046] The molar ratio of the compound P2 to the compound 3 is 1:1-1.5.
[0047] Furthermore, the present invention uses citric acid as a carbon source and ethylenediamine as a nitrogen source, and adopts a green and environmentally friendly one-step hydrothermal method to prepare nitrogen-doped green-emitting carbon quantum dots, and exemplarily provides a preparation method, which has the characteristics of low equipment requirements, simple operation, high yield, etc., and can directly produce carbon quantum dots with good water solubility, high stability, excellent fluorescence properties, small average particle size, and narrow particle size distribution. The specific steps are as follows:
[0048] The citric acid aqueous solution and the ethylenediamine aqueous solution were mixed and transferred to a polytetrafluoroethylene reactor for hydrothermal reaction. After the reaction was completed, the mixture was cooled and purified using a dialysis membrane with a molecular weight cutoff of 1000 Da. The nitrogen-doped carbon quantum dots were obtained by freeze-drying.
[0049] Furthermore, the reaction temperature of the hydrothermal reaction is 160-190° C., and the reaction time is 6-8 hours.
[0050] Furthermore, the citric acid aqueous solution and the ethylenediamine aqueous solution are mixed in a molar ratio of citric acid to ethylenediamine of 2:1-4, preferably 2:1.
[0051] Furthermore, the purification time is 1-3 days.
[0052] Furthermore, the average particle size of the carbon quantum dots is below 5 nm, and more than 70% of the carbon quantum dots have a particle size between 1.75 nm and 3.25 nm.
[0053] In order to achieve the third object, the present invention adopts the following technical solutions:
[0054] The invention discloses an application of the above-mentioned photoresist main material in preparing photoresist.
[0055] In order to achieve the fourth objective, the present invention adopts the following technical solutions:
[0056] The present invention discloses a photoresist composition comprising the photoresist main material as described above. The photoresist composition can be a positive photoresist composition or a negative photoresist composition.
[0057] Furthermore, the photoresist composition also includes a solvent, and the solvent is selected from one or more of propylene glycol methyl ether acetate, N,N-dimethylformamide, cyclohexanone, ethyl n-amyl ketone, ethyl isoamyl ketone, ethanol, acetonitrile, isopropanol, acetone, methyl n-amyl ketone, and methyl isoamyl ketone.
[0058] In one embodiment of the present invention, the photoresist composition is a single-component photoresist, which is composed of the compound shown in formula I and a solvent, that is, the photoresist composition includes only one photoresist component except the solvent, that is, it does not contain an acid generator except the compound shown in formula I.
[0059] In order to achieve the fifth object, the present invention adopts the following technical solutions:
[0060] The present invention discloses a photoresist coating comprising the photoresist composition as described above.
[0061] Furthermore, the photoresist composition is applied on the surface of the substrate by spin coating or drop coating to obtain a photoresist coating.
[0062] Furthermore, the substrate is made of silicon wafer or ITO glass.
[0063] In order to achieve the sixth object, the present invention adopts the following technical solutions:
[0064] The present invention discloses an application of the photoresist coating as described above in photolithography.
[0065] According to the present invention, the photoresist coating is used in modern lithography techniques such as 248 nm lithography, 254 nm lithography, 193 nm lithography, extreme ultraviolet (EUV) lithography, nanoimprint lithography or electron beam lithography.
[0066] The beneficial effects of the present invention are as follows:
[0067] (1) The present invention provides a series of novel photoresist main materials based on carbon quantum dot structure. The raw materials are cheap and easy to obtain, and the synthesis process is simple. The obtained photoresist main materials retain the original typical properties of carbon quantum dots, such as small particle size, narrow particle size distribution, high carbon content, etc. When preparing the photoresist main materials, the sp2 / sp3 hybridized carbon atoms of carbon quantum dots are used as the core, which maximizes the etching resistance of the main material, thereby effectively solving the problems of existing photoresist molecules being too large in size and having poor etching resistance, avoiding the introduction of metal elements to cause adverse effects on photolithography processing devices, and is conducive to meeting the requirements of high-resolution lithography.
[0068] (2) The photoresist main material provided by the present invention contains polar functional groups and has good solubility in polar solvents. A uniform thin film can be prepared by spin coating. When a solvent with a larger polarity is selected for development, the photoresist composition prepared using the photoresist main material can be used as a negative photoresist. If a solvent with a relatively small polarity is selected for development, the photoresist composition prepared using the photoresist main material can be used as a positive photoresist, and the prepared photoresist pattern has high resolution and low line edge roughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0070] Figure 1 The TEM image and particle size distribution diagram of the carbon quantum dots CQDs prepared in Example 1 of the present invention are shown. Figure 1 A is a TEM image, and B is a particle size distribution diagram.
[0071] Figure 2 The FT-IR spectra of the materials prepared in Example 1 and Example 2 of the present invention are shown, wherein: Figure 2 Wherein A is the CQDs of Example 1, B is compound A, C is compound B, and D is the photoresist main material (1).
[0072] Figure 3 The ultraviolet absorption spectrum and fluorescence spectrum of the carbon quantum dots CQDs prepared in Example 1 of the present invention are shown, wherein Figure 3 A is the ultraviolet absorption spectrum of CQDs, and B is the change of CQDs emission wavelength under different excitation wavelengths.
[0073] Figure 4 An AFM image of a thin film prepared using the photoresist main material (1) of Example 2 of the present invention is shown.
[0074] Figure 5The UV exposure pattern of the photoresist prepared using the photoresist main material (1) of Example 2 of the present invention is shown.
[0075] Figure 6 The electron beam lithography exposure pattern of the photoresist prepared using the photoresist main material (1) of Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0076] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0077] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0078] Example 1
[0079] Preparation of Carbon Quantum Dots (CQDs):
[0080] Weigh 1.58g of citric acid, add 25mL of deionized water, add 274μL of ethylenediamine (4.1mmol), stir the mixture magnetically for 30min, then transfer it to a polytetrafluoroethylene reactor and hydrothermally react at 180°C for 6 hours. After cooling to room temperature, the obtained solution was dialyzed for 2 days using a dialysis membrane (1000Da) and ultrapure water. After the dialyzed solution was freeze-dried at -48°C for 48 hours, the product carbon quantum dots CQDs were obtained, and the product was a reddish-brown powder with a mass of 0.62g and a yield of 39.2%.
[0081] The product CQDs were evaluated using TEM, FT-IR, UV-Vis, and fluorescence spectroscopy.
[0082] The morphology and particle size of CQDs were observed by transmission electron microscopy (TEM). Figure 1 As shown in the figure, CQDs are uniformly dispersed spherical particles with a particle size roughly ranging from 0.5 to 6.0 nm. 75% of the carbon quantum dots have a particle size between 1.75 nm and 3.25 nm, and the average particle size is about 2.61 nm.
[0083] Figure 2 The FT-IR results in (A) show that there are relevant functional groups such as hydroxyl, carboxyl and amino on the surface of CQDs, which give the material good stability and water solubility.
[0084] The UV absorption and fluorescence spectra of CQDs are shown in Figure 2. Figure 3 shown. Figure 3(A) is the UV-visible absorption spectrum. As shown in the figure, the UV-visible absorption spectrum of CQDs has two absorption peaks, located below 200nm and 344nm respectively. The UV absorption peak below 200nm is caused by the π→π* transition of the C=C bond in the carbon core of CQDs, and the absorption peak near 344nm is mainly caused by the n-π* transition of the C=O bond. Figure 3 The fluorescence spectrum in (B) shows that the optimal excitation and emission peaks of CQDs are located at 390nm and 482nm, respectively. When the excitation wavelength increases from 330nm to 500nm, the emission wavelength red-shifts; and when the excitation wavelength decreases from 330nm to 300nm, the emission wavelength blue-shifts, indicating that CQDs have excitation wavelength dependence.
[0085] Example 2
[0086] The preparation of the photoresist main material (1) is as follows:
[0087]
[0088] 1) Synthesis of Compound A:
[0089] 557 mg (4 mmol) of 4-aminoanisole was dissolved in 10 ml of 1.2 M hydrochloric acid aqueous solution, and the solution was cooled to 0-5 ° C. 1 ml of 4.4 M sodium nitrite was added under vigorous stirring. After reacting for 30 minutes, 6 ml of 4 M sodium hydroxide aqueous solution was added. The mixture was immediately added to 80 ml (concentration of 2.5 mg / ml) of CQDs aqueous solution at 90 ° C and under vigorous stirring. The reaction was continued for 10 minutes, and freeze-dried to obtain 1.8 g of brown-black product compound A. The FT-IR results were as follows: Figure 2 Middle (B).
[0090] 2) Synthesis of compound B:
[0091] 0.1 g of compound A was dissolved in 5 ml of DMF, 1 ml of diethyl carbonate and 1.03 g of 4-dimethylaminopyridine were added, and the mixture was stirred in an oil bath at 175°C for 18 hours. The product was extracted with ethyl acetate, washed with water, and the organic layer was separated and dried by adding anhydrous sodium sulfate. The brown product compound B was obtained by filtration and drying. The FT-IR result was Figure 2 Middle (C).
[0092] 3) Synthesis of photoresist main material (1):
[0093] 0.7 g of compound B was added to 20 ml of dichloromethane, and 1 ml of methyl trifluoromethanesulfonate was added. The mixture was reacted at room temperature for 24 hours. The insoluble matter was filtered out, and the filtrate was concentrated by rotary evaporation. After drying, 0.84 g of the product was obtained. The FT-IR result was Figure 2 (D). As can be seen from the figure, at 3276cm -1 、3091cm -1 Corresponding to NH stretching vibration, at 1657cm -1 Corresponding to C=O stretching vibration, at 1574cm -1 、1448cm -1 、1402cm -1 Corresponding to the stretching vibration of the benzene ring, at 1030cm -1 Corresponds to CO stretching vibration.
[0094] Example 3
[0095] The preparation of the photoresist main material (2) is as follows:
[0096]
[0097] 1) Synthesis of compound C:
[0098] 0.8 g (4 mmol) of 4-(phenylthio)aniline was dissolved in 20 ml of 1.2 M aqueous hydrochloric acid solution. The solution was cooled to 0-5°C, and 1 ml of 4.4 M sodium nitrite was added under vigorous stirring. After reacting for 30 minutes, 6 ml of 4 M aqueous sodium hydroxide solution was added. The mixture was immediately added to 80 ml (concentration of 2.5 mg / ml) of CQDs aqueous solution at 90°C under vigorous stirring, and reacted for 10 minutes. The solution was freeze-dried to obtain 2.9 g of a brown product compound C.
[0099] 2) Synthesis of compound D:
[0100] Dissolve 0.13 g of compound C in 5 ml of DMF, add 1 ml of diethyl carbonate and 1.03 g of 4-dimethylaminopyridine, stir in an oil bath at 175°C, react for 18 hours, extract the product with ethyl acetate, wash with water, separate the organic layer, add anhydrous sodium sulfate to dry, filter and dry, and obtain 0.19 g of brown product compound D.
[0101] 3) Synthesis of photoresist main material (2):
[0102] 0.7 g of compound D was added to 20 ml of dichloromethane, and 1 ml of methyl trifluoromethanesulfonate was added. The mixture was reacted at room temperature for 24 hours. The insoluble matter was filtered out, and the filtrate was concentrated by rotary evaporation and dried to obtain 0.75 g of the product.
[0103] Example 4
[0104] The preparation of the photoresist main material (3) is as follows:
[0105]
[0106] 1) Synthesis of compound E:
[0107] 0.61 g (4 mmol) of 4-(ethylmercapto)aniline was dissolved in 20 ml of 1.2 M aqueous hydrochloric acid solution. The solution was cooled to 0-5°C, and 1 ml of 4.4 M sodium nitrite was added under vigorous stirring. After reacting for 30 minutes, 6 ml of 4 M aqueous sodium hydroxide solution was added. The mixture was immediately added to 80 ml (concentration of 2.5 mg / ml) of CQDs aqueous solution at 90°C with vigorous stirring. The mixture was reacted for 10 minutes and freeze-dried to obtain 2.9 g of dark brown product compound E.
[0108] 2) Synthesis of Compound F:
[0109] Dissolve 0.11 g of compound E in 5 ml of DMF, add 1 ml of diethyl carbonate and 1.03 g of 4-dimethylaminopyridine, stir in an oil bath at 175°C, react for 18 hours, extract the product with ethyl acetate, wash with water, separate the organic layer, add anhydrous sodium sulfate to dry, filter and dry to obtain 0.15 g of a brown product compound F.
[0110] 3) Synthesis of photoresist main material (3):
[0111] 0.15 g of compound F was added to 10 ml of dichloromethane, and 1 ml of methyl trifluoromethanesulfonate was added. The mixture was reacted at room temperature for 24 hours. The insoluble matter was filtered out, and the filtrate was concentrated by rotary evaporation and dried to obtain 0.1 g of the product.
[0112] Example 5
[0113] The photoresist main material (1) prepared in Example 2 was dissolved in acetonitrile to obtain a solution with a concentration of 20 mg / ml, and then filtered with a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution. The spin coating solution was spin-coated on a silicon substrate to form a film, and the uniformity and flatness of the film were analyzed by AFM. The results are shown in FIG. Figure 4 It can be seen from the figure that the obtained film is very uniform and has no crystallization phenomenon, which is conducive to the preparation of a smooth surface lithography pattern.
[0114] Example 6: A negative photoresist formulation and its application in UV lithography
[0115] The photoresist main material (1) prepared in Example 2 was dissolved in acetonitrile to obtain a solution with a concentration of 20 mg / ml, and filtered through a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution. The spin coating solution was spin-coated on a silicon substrate to form a film, and baked at 80°C for 3 minutes. The prepared film was exposed to an exposure experiment (254 nm ultraviolet lamp) for 1 minute, and then developed using water: isopropanol = 2:1 (V / V). The results are shown in FIG. Figure 5 , very clear stripes can be obtained, and the width of the photolithography stripes is 1μm, indicating that the prepared photoresist pattern has high resolution and low line edge roughness.
[0116] Example 7: A negative photoresist formulation and its application in electron beam lithography
[0117] The photoresist main material (1) prepared in Example 2 was dissolved in acetonitrile to obtain a solution with a concentration of 15 mg / ml, and filtered through a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution. The spin coating solution was spin-coated on a silicon substrate to form a film, and baked at 80°C for 3 minutes. The prepared film was subjected to an exposure experiment (electron beam lithography) with an exposure dose of 3200 μC / cm 2 , then use water: isopropanol = 2:1 (V / V) to develop for 1 minute, the results are shown in Figure 6 , very clear stripes were obtained, and the minimum width of the photolithography stripes was 40nm, indicating that the prepared photoresist pattern had high resolution and low line edge roughness.
[0118] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A photoresist main material based on carbon quantum dots, characterized in that: The general structure of the photoresist main material is shown in Formula I: Among them, R A Selected from H, C 1-15 Alkyl, C 1-15 Alkoxy, C 3-20 Any one of a cycloalkyl group and a 3- to 20-membered heterocyclic group; R B , R C The same or different, independently selected from H, C 1-15 Alkyl, C 3-20 Cycloalkyl, C 6-20 aryl, 5- to 20-membered heteroaryl, 3- to 20-membered heterocyclyl, -C 1-15 Alkyl-C 6-20 Aryl, -C 1-15 Alkyl-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 6-20 Aryl, -C 1-15 Alkyl-CO-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 1-15 Alkyl, -C 1-15 Alkyl-CO-C 3-20 Any of the cycloalkyl groups; X - represents an anion selected from any one of halide, carboxylate, sulfate, alkyl sulfonate, haloalkyl sulfonate, p-toluenesulfonate, tetrafluoroborate, hexafluoroantimonate, hexafluorophosphate, and bis(trifluoromethanesulfonyl)imide; Represents the carbon quantum dot structure with side groups.
2. The photoresist main material according to claim 1, characterized in that: The R A Select from H or C 1-8 alkyl; The R B Selected from H, C 1-6 Alkyl, C 6-12 Any of the aromatic groups; The R C Select from H or C 1-8 alkyl.
3. The photoresist main material according to claim 1, characterized in that: The photoresist main material is selected from one of the following structures:
4. The method for preparing a photoresist main material according to any one of claims 1 to 3, characterized in that: The steps include: Dissolve compound 1 in a hydrochloric acid aqueous solution, cool to 0-5°C, add sodium nitrite, react for 0.5-1 hour, add a sodium hydroxide aqueous solution to obtain a reaction solution; The reaction solution was added into a carbon quantum dot aqueous solution for reaction, and the compound P1 was obtained after freeze-drying; Dissolve compound P1 in a solvent, add compound 2 and 4-dimethylaminopyridine, stir in an oil bath, react for 18-20 hours, extract the product with ethyl acetate, wash with water, dry the organic phase over sodium sulfate, and remove the solvent by rotary evaporation to obtain compound P2; Compound P2 is added to a solvent, and compound 3 is added, reacted at room temperature for 12-24 hours, filtered, and the filtrate is concentrated by rotary evaporation and recrystallized to obtain a compound of formula I; Wherein, the structures of compounds 1-3, P1, and P2 are as follows: R A Selected from H, C 1-15 Alkyl, C 1-15 Alkoxy, C 3-20 Any one of a cycloalkyl group and a 3- to 20-membered heterocyclic group; R B , R C The same or different, independently selected from H, C 1-15 Alkyl, C 3-20 Cycloalkyl, C 6-20 aryl, 5- to 20-membered heteroaryl, 3- to 20-membered heterocyclyl, -C 1-15 Alkyl-C 6-20 Aryl, -C 1-15 Alkyl-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 6-20 Aryl, -C 1-15 Alkyl-CO-5 to 20 membered heteroaryl, -C 1-15 Alkyl-CO-C 1-15 Alkyl, -C 1-15 Alkyl-CO-C 3-20 Any of the cycloalkyl groups; X is selected from any one of halogen, carboxyl, sulfonyl, alkylsulfonyl, halogenated alkylsulfonyl, p-toluenesulfonyl, tetrafluoroboric acid, hexafluoroantimonic acid, hexafluorophosphate, and bis(trifluoromethanesulfonyl)imide groups; Preferably, the molar ratio of the compound 1, sodium nitrite and carbon quantum dots is 1:0.8-1.2:0.1-1; The molar ratio of the compound P1, the compound 2 and 4-dimethylaminopyridine is 1:1-10:0.1-1; The molar ratio of the compound P2 to the compound 3 is 1:1-1.
5.
5. The preparation method according to claim 4, characterized in that: The carbon quantum dots are prepared according to the following steps: The citric acid aqueous solution and the ethylenediamine aqueous solution were mixed and transferred to a polytetrafluoroethylene reactor for hydrothermal reaction. After the reaction was completed, the mixture was cooled, purified using a dialysis membrane with a molecular weight cutoff of 1000 Da, and freeze-dried to obtain nitrogen-doped carbon quantum dots. Preferably, the reaction temperature of the hydrothermal reaction is 160-190° C., and the reaction time is 6-8 hours; Preferably, the citric acid aqueous solution and the ethylenediamine aqueous solution are mixed in a molar ratio of citric acid to ethylenediamine of 2:1-4; Preferably, the purification time is 1-3 days; Preferably, the average particle size of the carbon quantum dots is below 5 nm, and more than 70% of the carbon quantum dots have a particle size between 1.75 and 3.25 nm.
6. Use of the photoresist main material according to any one of claims 1 to 3 in the preparation of photoresist.
7. A photoresist composition, characterized in that Comprising the photoresist main material as claimed in any one of claims 1 to 3; Preferably, the photoresist composition further comprises a solvent, and the solvent is selected from one or more of propylene glycol methyl ether acetate, N,N-dimethylformamide, cyclohexanone, ethyl n-amyl ketone, ethyl isoamyl ketone, ethanol, acetonitrile, isopropanol, acetone, methyl n-amyl ketone, and methyl isoamyl ketone.
8. A photoresist coating, characterized in that Comprising the photoresist composition as claimed in claim 7.
9. The photoresist coating according to claim 8, characterized in that: Applying the photoresist composition on the surface of the substrate by spin coating or drop coating to obtain a photoresist coating; Preferably, the substrate is made of silicon wafer or ITO glass.
10. Use of the photoresist coating according to claim 8 or 9 in photolithography.